Assessing Reaction Mechanisms of Graphite Negative Electrodes Based on Operando Synchrotron Radiation Diffraction Data. Issue 4 (6th April 2021) - Fujimoto, Hiroyuki; Kiuchi, Hisao; Takagi, Shigeharu; Shimoda, Keiji; Okazaki, Ken-ichi; Ogumi, Zempachi; Abe, Takeshi
Abstract : Since the commercialization of rechargeable Li ion batteries in the early 1990 s, the performance of these devices has continually improved. In such batteries, graphite is typically used as the negative electrode and the present work examined the reaction mechanisms at graphite negative electrodes based on operando synchrotron X-ray diffraction analyses during charge/discharge. The resulting in-plane diffraction patterns of the Li-intercalated graphite permitted a detailed analysis of changes in the three-dimensional structure of the electrode. As the intercalation proceeded from a dilute stage 1 (with less Li intercalation) to a final stage 1 (the formation of LiC6 ), the material transitioned from a random in-plane structure to a p(√3 × √3)R30° in-plane structure via a superlattice based on a p(3 × 3)R0° in-plane structure. The data also indicate that a series of superlattices was formed during the reaction of the electrode as a result of successive rearrangements, depending on the amount of Li intercalated into the graphite.